Induction of xenobiotic-metabolizing enzymes in hepatocytes by beta-naphthoflavone: Time-dependent changes in activities, protein and mRNA levels - Lněničková Kateřina; Skálová Lenka; Stuchlíková Lucie; Szotáková Barbora; Matoušková Petra (Acta Pharmaceutica)
In the present study, time-dependency of the induction effect of a selective inducer on the activity, protein and mRNA levels of cytochromes P450 1A1/2 (CYP1A1/2), NAD(P)H:quinone oxidoreductase 1 (NQO1) and glutathione S-transferases (GSTA), in primary culture of rat hepatocytes was tested and evaluated. To show the differences in responses of tested enzymes, the common aryl hydrocarbon receptor (AhR) ligand agonist, beta-naphthoflavone (BNF), was used. Induction of CYP1A1/2 by BNF was detected at all time intervals and at all levels (i.e., mRNA, protein, enzyme activity). Different responses of NQO1 and GSTA upon BNF treatment were observed. Our results demonstrate that the responses of different xenobiotic-metabolizing enzymes to the inducer vary in time and depend on the measured parameter. For these reasons, an induction study featuring only one-time interval treatment and/ or one parameter testing could produce misleading information.